2018
DOI: 10.3390/mti2040074
|View full text |Cite
|
Sign up to set email alerts
|

Participatory Prototyping to Inform the Development of a Remote UX Design System in the Automotive Domain

Abstract: This study reports on the empirical findings of participatory design workshops for the development of a supportive automotive user experience design system. Identifying and addressing this area with traditional research methods is problematic due to the different user experience (UX) design perspectives that might conflict and the related limitations of the automotive domain. To help resolve this problem, we conducted research with 12 user experience (UX) designers through individual participatory prototyping … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
(65 reference statements)
1
2
0
Order By: Relevance
“…Although including goals, progress, and opportunities for socialization are effective techniques, similar to other studies we found that the app should be designed using a minimalistic design approach [62]. In workshop 2, our participants reported preferring minimal design.…”
Section: Principal Findingssupporting
confidence: 80%
“…Although including goals, progress, and opportunities for socialization are effective techniques, similar to other studies we found that the app should be designed using a minimalistic design approach [62]. In workshop 2, our participants reported preferring minimal design.…”
Section: Principal Findingssupporting
confidence: 80%
“…Self-driving cars have long been part of various visions of our society's future, promising comfortable, accessible and sustainable mobility for everyone (ERTRAC, 2019). With recent advances in technology (especially computer systems and artificial intelligence) paving the way to intelligent mobility systems (Tasoudis and Perry, 2018;Araujo et al, 2019), this vision has moved into closer reach. The progress in driving automation can be classified according to the distribution of driving-related tasks between human driver and automated driving system.…”
Section: Introductionmentioning
confidence: 99%
“…Even though potential future users state a general openness to driving automation (Fraedrich and Lenz 2015), they also report profound reservations toward the technology and its safety (Schoettle and Sivak, 2014;Kyriakidis et al, 2015;Wolf, 2016), which question a sufficient usage and dissemination level of automated vehicles. These reservations are attributed to the loss of control and the fundamental change of the in-vehicle user experience (shifting from an active driver experience to a passive passenger experience) that are provoked by handing over vehicle control to an automated system (Elbanhawi et al, 2015;Tasoudis and Perry, 2018). Consequently, the direction in which future mobility will develop will not only be decided by technical advances and accompanying societal and legal measures (Littman, 2020), but substantially by human factors (Kyriakidis et al, 2017;Shariff et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Development teams may address user needs iteratively throughout the development process and guarantee that design decisions are continuously validated and refined by incorporating UX design activities into Agile iterations. Because of the culture of constant learning and adaptation that this iterative method promotes, software solutions that dynamically adapt to changing user needs and market demands are produced (Tasoudis & Perry, 2018).…”
Section: Major Findingsmentioning
confidence: 99%